Design and development of a mobile robotic system for aircraft wing fuel tank inspection - Dhoot, Manpreet kaur; Fan, Ip-Shing (Society of Automotive Engineers (SAE), 2022)
This paper presents the design concept behind a novel remote visual inspection robotic system for fighter jet aircraft wing fuel tank inspection. This work is part of a larger research project which focuses on design, simulation, physical prototyping and experimental validation of a robotic system. Whereas this paper specifically focuses on the development concept of locomotion design choice for the robot. Therefore without an effective mobility method the robot will not be able to fulfill its purpose to access the hazardous confined spaces of the fuel tank. Aircraft wing fuel tank inspection is a challenging area of maintenance which requires a considerable amount of preparation and involvement of several tasks in order to conduct effective Visual and Non Destructive Inspection. The environment of an aircraft wing fuel tank poses several challenges due to both physical and atmospheric constraints which can be detrimental to human personal. This paper introduces an effective locomotion design which should allow the robot to enter and maneuver within confined spaces. The robot is relatively small, approximately 70mm in height and width yet, flexible enough to move within the restricted spaces of the wing. The mobile robot platform is a combination of small track systems that articulate like a snake. An additional mobile platform deploys an inspection sensor to reach the spaces that are unreachable by the robot body. Like other proposed robotic systems this particular proposal differs as it allows the robot to enter from the root of the wing and reach the narrower spaces towards with the wing tip. This paper highlights the stakeholder requirements to illustrate the foundation of the robotic system design. An overview of current complications of wing fuel tank inspection is presented and the analysis of current proposed robotic systems for wing fuel tank inspection. An engineering design methodology approach is followed for this project. Several locomotion methods are evaluated and an innovative locomotion method is illustrated with the use of CAD models. The desired outcome of this research is to eliminate the entry or close contact with the fuel tank by human personal.